Carbide-bonded graphene coating of mold insert for rapid thermal cycling in injection molding. (25th July 2017) - Xie, Pengcheng; Yang, Huaguang; Zhao, Yungui; Yu, Wenxia; Cheng, Lisheng; Yang, Weimin; Yan, Hua; Tan, Jing
Highlights: Graphene coatings were prepared for rapid thermal cycling in injection molding. Average and transient heating rates could reach 11.6 °C/s and 16.1 °C/s. The elongation at yield and the tensile strength of products were increased by 265.11% and 37.77% Abstract: A novel carbide-bonded graphene coating on silicon insert was proposed to realize rapid thermal cycling (RTC) in injection molding. Continuous and dense carbon-bonded graphene coating was prepared on the surface of the silicon cavity through chemical vapor deposition. Serving as a thin-film resistance heater, the graphene coating was able to heat the mold cavity rapidly to above the glass-transition temperature of the polymer, even if the applied power source was of relatively low voltage. When the voltage was 240 V, the coating was heated up to 145.6 °C in a short period of 10 s, that is, the average and transient heating rates were able to be as high as 11.6 °C/s and 16.1 °C/s, respectively. This injection molding technique of RTC was successfully implemented to produce plate samples with uniform sizes in thickness (600 μm). The influence of RTC on weld line, internal stress, and replication fidelity was also investigated. Compared with conventional injection molding, our facile method was able to mold products with smaller weld mark, less internal stress, and better replication fidelity. The tensile strength and elongation at yield of the products were also enhanced by 37.77% and increased by 265.11%, respectively, with much less energy consumption.